Turkey Sire Effects on Embryonic Survival and Physiology - Christensen, Vern. L.; Ort, Debbie. T.; Wineland, Mike. J.; Grimes, Jesse. L. (International Journal of Poultry Science, 2003)
Sire effects on turkey embryonic survival and growth are not well understood. In avian species, the sire may play only a minor role in embryonic growth as dam effects, mediated through physical and functional qualities of eggs, are thought to be the main determinants. Very little is known of separate dam and sire influences on embryonic survival. The hypothesis was proposed that sires from lines with different BW and embryonic survival rates when mated to an unrelated dam line would produce embryos with different survival, growth and metabolism. Sires from a line with light BW but good embryonic survival (LBW) or sires from a heavy BW line and poor embryonic survival (HBW) were mated to dams of the same unrelated line. Sires from the dam line were included as a control group (Controls). Hens were randomly assigned to sires and inseminated identically at weekly intervals with semen from the assigned sire line. Eight biweekly settings of eggs were placed into incubators to test embryonic survival rates among the sire lines. Tissues were sampled at designated intervals during the experiment to assess the physiological basis for embryonic survival. Contrary to our hypothesis, embryos from the HBW sire line had the best survival compared to LBW and Control. Although LBW poults were from smaller sires, they weighed more than HBW poults. During development LBW sire embryos stored greater amounts of glycogen and lactate in liver and muscle. No effects were seen in cardiac tissue. BW differences were related to greater yolk, but the differences in organ weights and metabolism were clearly related to sire. Thus, sire DNA may direct organ growth and function and influence embryonic survival.